Impact of long-term steroid therapy on epicardial and pericardial fat deposition: a cardiac MRI study. Issue 1 (December 2015) - Kitterer, Daniel; Latus, Joerg; Henes, Joerg; Birkmeier, Stefan; Backes, Maik; Braun, Niko; Sechtem, Udo; Dominik Alscher, M.; Mahrholdt, Heiko; Greulich, Simon
Abstract Background Increased cardiac fat has been identified as a risk factor for coronary artery disease. Metabolic syndrome is associated with increased cardiac fat deposition. Steroids are known to imitate some effects of metabolic syndrome and are frequently used in patients with rheumatic disorders. Primary aim was to evaluate the impact of long-term steroid use on cardiac fat deposition in patients with rheumatic disorders. In addition, we sought to investigate if this effect might be dose-dependent. Methods Patients were enrolled as follows: (1) rheumatic disorder; and (2) long-term steroid therapy, and (3) underwent cardiovascular magnetic resonance (CMR) imaging. Patients were stratified in a high-dose (>7.5 mg prednisone equivalent/day for at least 6 months) and a low-dose steroid group (<7.5 mg prednisone equivalent/day) and compared to steroid-naïve controls without rheumatic disorders. Results 122 patients were included (n = 61 steroid patients, n = 61 controls). N = 36 were classified as high-dose, n = 25 as low-dose steroid group. Steroid patients showed larger epicardial 5.7 [3.5–9.1] cm2 and pericardial 13.0 [6.1–26.8] cm2 areas of fat than controls 4.2 [1.3–5.8] cm2 /6.4 [1.6–15.4] cm2, p < 0.001, p < 0.01, respectively. High-dose steroid patients had more epi- and pericardial fat both than controls: 7.2 [4.2–11.1] cm2 vs. 4.4 [1.0-6.0] cm2, p < 0.001; 18.6 [8.9–38.2] cm2 vs. 10.7 [4.7–26.8] cm2, p < 0.05, and patients in the low-dose steroid group (p < 0.01, p < 0.001, respectively). Conclusion The present data suggest increased cardiac fat deposition in steroid-treated patients with rheumatic disorders. Furthermore, this accumulation of cardiac fat seems to be dose-dependent, pointing towards a cumulative effect of steroids.